Expression of Human ACE2 in Lactobacillus and Beneficial Effects in Diabetic Retinopathy in Mice - Verma, Amrisha (Mol Ther Methods Clin Dev, 2019)
The angiotensin converting enzyme 2 (ACE2) catalyzes the degradation of Angiotensin II (Ang II) to generate Angiotensin-(1-7), which reduces inflammation and oxidative stress stimulated by Ang II. ACE2 has been shown to be protective in cardiovascular and metabolic diseases including diabetes and its complications. However, the challenge for its clinical application is large-scale production of high-quality ACE2 with sufficient target tissue bioavailability. We developed an expression and delivery system based on the use of probiotic species Lactobacillus paracasei (LP) to serve as a live vector for oral delivery of human ACE2. We show that codon-optimized ACE2 can be efficiently expressed in LP. Mice treated with the recombinant LP expressing the secreted ACE2 in fusion with the non-toxic subunit B of cholera toxin, which acts as a carrier to facilitate transmucosal transport, showed increased ACE2 activities in serum and tissues. ACE2-LP administration reduced the number of acellular capillaries, blocked retinal ganglion cell loss, and decreased retinal inflammatory cytokine expression in two mouse models of diabetic retinopathy. These results provide proof of concept for feasibility of using engineered probiotic species as live vector for delivery of human ACE2 with enhanced tissue bioavailability for treating diabetic retinopathy, as well as other diabetic complications.